Degradation and mechanism analysis of chloroxylenol in aqueous solution by gas–liquid discharge plasma combined with ozonation. Issue 21 (6th April 2021) - Ma, Keke; Zhou, Lu; Bai, Yu; Xin, Yiying; Chen, Mingru; Li, Heping; Bao, Chengyu; Zhou, Yuexi
Abstract : Gas–liquid discharge non-thermal plasma (NTP) coupled with an ozonation reactor was used to investigate the removal of a broad-spectrum antibacterial agent, chloroxylenol (PCMX), from aqueous solution. Abstract : Gas–liquid discharge non-thermal plasma (NTP) coupled with an ozonation reactor was used to investigate the removal of a broad-spectrum antibacterial agent, chloroxylenol (PCMX), from aqueous solution. Under the same experimental conditions (discharge power of 50.25 W, the initial concentration of PCMX of 60 mg L −1, oxygen flow of 1.0 L min −1 and PCMX solution flow of 150 mL min −1 ), the PCMX degradation rates in the ozonation-only, NTP-only and NTP/O3 systems were 29.25%, 67.04% and 79.43%, respectively. Correspondingly, the energy efficiency has also been greatly improved, and increased to 0.45, 1.03 and 1.21 g kW −1 h −1 . In addition, the effects of the initial concentration of PCMX, initial pH, the flow rate of oxygen, the addition of H2 O2 and the addition of a radical scavenger on the degradation rate of PCMX were investigated in the NTP/O3 system. The degradation rate in acidic solutions was higher than that in alkaline solutions. During the removal process of PCMX, the rate of degradation was strongly increased with the addition of H2 O2 and acutely decreased with the addition of the radical scavenger. Compared with deionized water the degradation rates of PCMX in secondary effluent were inhibited. Four main intermediates of PCMX degradation by the NTP/O3 system were identified by gas chromatography-mass spectrometry (GC-MS) and a possible degradation pathway of PCMX was proposed. The changes in toxicity of the PCMX solution during the NTP/O3 system oxidation process were also evaluated using bioluminescent bacteria and Quantitative Structure Activity Relationship (QSAR) models with the help of the ECOSAR software.